The Kuril Islands dispute : Impact on Japan-Russia relations - Cahová, Lucie (2023)
The Kuril Islands dispute is one of the major reasons for the discourse between Japan and Russia and is also one of the causes of why Japan and Russia still not have signed a peace treaty after World War II. Most research on this subject is focused on only one side of the dispute, not taking into account arguments from both viewpoints. There has also been a lack of suggestions on how to resolve the issue. Using comparative discourse analysis examining the foreign policies and arguments from each side the paper aims to find a theoretical resolution. According to the analysis to resolve the conflict there will have to be a shift in priorities as both sides are willing to compromise, but the conditions would have to be set to accommodate both Japan and Russia. According to the analysis the most ideal resolution would be for Japan to receive the two islands Habomai and Shikotan and for issue of the two bigger islands to be left for later.